2016
DOI: 10.1021/acs.joc.6b00441
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Benzyl Aryl Carbonates: The Role of Cation−π Interactions

Abstract: Benzyl aryl carbonates can react with a nucleophile to yield an activated electrophile and an aryloxide anion. Previously, we had utilized this in the synthesis of α-nitro esters from nitroalkanes. To further understand the process of activation of these carbonates by nucleophiles, we have performed kinetic studies on the hydrolysis of carbonates using nucleophiles. Rate constants for the hydrolysis were obtained under pseudo-first-order conditions with DABCO as the nucleophile. A comparison of rate constant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…This indicates that the transition state TS-329 is stabilized by a cation−π interaction between the ammonium and the phenyl moiety as shown in Scheme 81. 246…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the transition state TS-329 is stabilized by a cation−π interaction between the ammonium and the phenyl moiety as shown in Scheme 81. 246…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Rajaram et al found that the rate of hydrolysis for p- methoxybenzyl phenyl carbonate 328 with DABCO is 16-fold faster than that for isobutyl phenyl carbonate 327 (Scheme ). This indicates that the transition state TS- 329 is stabilized by a cation−π interaction between the ammonium and the phenyl moiety as shown in Scheme …”
Section: Reactions Involving Cationic Intermediates or Transition Statesmentioning
confidence: 99%
“…As can be seen in Scheme 2, first, deprotonation of phenyl α ‐cyano arylacetate 1 with DABCO generated an enolate and attack of the enolate to quinone monoimine 2 a generated adduct A which underwent aromatization and protonization to give the adduct B . Following nucleophilic addition of DABCO to the carbonyl group [7] afforded zwitterion C . Then C−C cleavage of C produced carbanion D and amonium cation E which was hydrolyzed to give protonized BABCO, phenol and carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…Deuterium-labeled molecules are significant tools for the study of metabolic pathways and reaction mechanisms as interior standards in analytical protocols . Deuterium is generally used in isotope labeling and as the primary source for determining the kinetic isotope effects in mechanistic studies .…”
Section: Introductionmentioning
confidence: 99%